Decomposing firm-product appeal: How important is consumer taste? - Bee-Yan Aw; Yi Lee; Hylke Vandenbussche (National Bank of Belgium, 2018)
We develop and structurally estimate a trade model in order to identify the importance of consumer taste. The model separates taste from quality and productivity (TFPQ) at the firm-product level. Export data by destination countries allow us to identify the level of taste from consumer heterogeneity across destinations. We decompose export revenue into the contribution of taste, quality and costs. We find that taste is very important and explains about 50 % of the variation in export revenue. Productivity (TFPQ) differences between firm-products become more prominent than taste in explaining export success only when the cost elasticity of improving quality is high.
Keywords: F12; F14; 330; tastes; quality; productivity; exports; firm-product